Immunity-Related Protein Expression and Pathological Lung Damage in Mice Poststimulation with Ambient Particulate Matter from Live Bird Markets - Meng, Kai; Wu, Bo; Gao, Jing; Cai, Yumei; Yao, Meiling; Wei, Liangmeng; Chai, Tongjie (Frontiers in Immunology, 2016)
The objective of this study was to obtain insight into the adverse health effects of airborne particulate matter (PM) collected from live bird markets (LBM) and to determine whether biological material in PM accounts for immune-related inflammatory response. Mice were exposed to a single or repeated dose of PM, after which the expression of Toll-like receptors (TLRs), cytokines, and chemokines in the lungs of infected mice were examined by enzyme-linked immunosorbent assay and histopathological analysis. Results after single and repeated PM stimulation with PM2.5+, PM2.5-, PM10+, and PM10- indicated that TLR2 and TLR4 played a dominant role in the inflammatory responses of the lung. Further analysis demonstrated that the expression levels of IL-1β, TNF-α, IFN-γ, IL-8, IP-10, and MCP-1 increased significantly, which could eventually contribute to lung injury. Moreover, biological components in PM were critical in mediating immune-related inflammatory responses and should therefore not be overlooked.